Follow-up and transition of care for low recurrence risk thyroid cancer patients in Canada - Ralf Paschke; Sana Ghaznavi; Syed Ali Imran; Jennifer Jacquier; Heather Lochnan; Marie-Hélène Massicotte; Elliot Mitmaker; Deric Morrison; Vicki Munro; Michelle Sveistrup; Sam M Wiseman; Afshan Zahedi (European Thyroid Journal)
The incidence of differentiated thyroid cancer (DTC) has increased significantly in recent decades. Following initial diagnosis, DTC patients are classified according to the American Thyroid Association (ATA) as low, intermediate, and high risk for recurrence. Patients in the ATA low recurrence-risk category have a recurrence risk of ≤5%, with 20-year disease-specific mortality of <1%. Accordingly, there has been a shift to de-escalating initial treatment, including the relaxation of thyroid-stimulating hormone suppression. In addition, fewer low-risk patients undergo total thyroidectomy or radioactive iodine therapy. However, the optimal long-term surveillance strategy remains unclear, with many patients continuing follow-up in speciality clinics for many years. In addition, emerging evidence suggests that long-term surveillance can be effectively managed in primary care settings. To enhance understanding among Canadian thyroid practitioners and to improve care for Canadian patients diagnosed with low-risk DTC, we developed this consensus statement by collecting feedback from a multidisciplinary team led by one chairperson (endocrinologist), an additional eight endocrinologists, two surgeons, and one patient partner. This consensus statement reflects current evidence and expert opinion regarding initial management and long-term surveillance of low-risk DTC patients. This work is valuable to Canadian thyroid practitioners as it provides standardized guidelines to ensure optimal care and improved outcomes for low-risk DTC patients.